Intégration symbolique à Fès et ancrages sur l’ailleurs : Les Africains subsahariens et leur rapport à la zaouïa d’Ahmad al-Tijânî - Johara Berriane (L’Année du Maghreb)
The article questions the role of the zawiya of Ahmad al-Tijani in the everyday life and the trajectories of sub-Saharan migrants and students living in Fez. Based on an ethnographic research carried out in and around that sanctuary-mosque and qualitative interviews conducted with migrants and students, it analyses the function, role and place that this West-African pilgrimage site has for sub-Saharan residents of Fez. The article begins with a description of the physical space of the zawiya and analyses its embeddedness in both the local religious topography and the transnational Tijani territories. It then explores the relationships that sub-Saharan residents have with the zawiya: first, this place symbolizes an African presence in Fez; second, it takes the role of a space of integration and intercultural sociability for them. Finally, African residents develop a sense of belonging and ownership of the zawiya and its saint, largely due to the influence of the Tijaniyya in West-African countries and the way black Africans are welcomed in this religious site.